Nickel absorption and kinetics in human volunteers - Sunderman, Jr, F W; Hopfer, S M; Sweeney, K R; Marcus, A H; Most, B M; Creason, J (Proceedings of the Society for Experimental Biology and Medicine, 1989)
Mathematical modeling of the kinetics of nickel absorption, distribution, and elimination was performed in healthy human volunteers who ingested NiSO4 drinking water (Experiment 1) or added to food (Experiment 2). Nickel was analyzed by electrothermal atomic absorption spectrophotometry in serum, urine, and feces collected during 2 days before and 4 days after a specified NiSO4 dose (12 micrograms of nickel/kg, n = 4; 18 micrograms of nickel/kg, n = 4; or 50 micrograms of nickel/kg, n = 1). In Experiment 1, each of the subjects fasted 12 hr before and 3 hr after drinking one of the specified NiSO4 doses dissolved in water; in Experiment 2, the respective subjects fasted 12 hr before consuming a standard American breakfast that contained the identical dose of NiSO4 added to scrambled eggs. Kinetic analyses, using a compartmental model, provided excellent goodness-of-fit for paired data sets from all subjects. Absorbed nickel averaged 27 +/- 17% (mean +/- SD) of the dose ingested in water vs 0.7 +/- 0.4% of the same dose ingested in food (a 40-fold difference); rate constants for nickel absorption, transfer, and elimination were not significantly influenced by the oral vehicle. The elimination half-time for absorbed nickel averaged 28 +/- 9 hr. Renal clearance of nickel averaged 8.3 +/- 2.0 ml/min/1.73 m2 in Experiment 1 and 5.8 +/- 4.3 ml/min/1.73 m2 in Experiment 2. This study confirms that dietary constituents profoundly reduce the bioavailability of Ni2+ for alimentary absorption; approximately one-quarter of nickel ingested in drinking water after an over-night fast is absorbed from the human intestine and excreted in urine, compared with only 1% of nickel ingested in food. The compartmental model and kinetic parameters provided by this study will reduce the uncertainty of toxicologic risk assessments of human exposures to nickel in drinking water and food.